2012
DOI: 10.1016/j.celrep.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Confinement to Organelle-Associated Inclusion Structures Mediates Asymmetric Inheritance of Aggregated Protein in Budding Yeast

Abstract: The division of the S. cerevisiae budding yeast, which produces one mother cell and one daughter cell, is asymmetric with respect to aging. Remarkably, the asymmetry of yeast aging coincides with asymmetric inheritance of damaged and aggregated proteins by the mother cell. Here, we show that misfolded proteins are retained in the mother cell by being sequestered in juxtanuclear quality control compartment (JUNQ) and insoluble protein deposit (IPOD) inclusions, which are attached to organelles. Upon exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
272
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 188 publications
(293 citation statements)
references
References 28 publications
18
272
3
Order By: Relevance
“…Several studies have provided key insight into the identities of senescence factors by studying the asymmetric segregation of damage in singlecell organisms that rejuvenate the emerging generation by preventing the inheritance of damaged factors such as DNA, lipids, and proteins (1, 4, 5). In particular, a number of seminal studies have demonstrated that bacteria and yeast use a complex and multifaceted machinery to prevent the inheritance of damaged and aggregated proteins by the new generation by restricting them to the older lineage during cell division (1,6,7).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have provided key insight into the identities of senescence factors by studying the asymmetric segregation of damage in singlecell organisms that rejuvenate the emerging generation by preventing the inheritance of damaged factors such as DNA, lipids, and proteins (1, 4, 5). In particular, a number of seminal studies have demonstrated that bacteria and yeast use a complex and multifaceted machinery to prevent the inheritance of damaged and aggregated proteins by the new generation by restricting them to the older lineage during cell division (1,6,7).…”
mentioning
confidence: 99%
“…Upon misfolding, substrates localize to transient stress foci (SFs), which concentrate chaperones, holdases, and disaggregases (7). SFs are dynamic IBs that form in response to acute stress and may participate in the triage decision of whether to refold, degrade, or aggregate misfolded proteins (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations